2013
DOI: 10.1371/journal.pone.0074280
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Methylated Seed Oil on Enhancing Biological Efficacy of Topramezone on Weeds

Abstract: Methylated seed oil (MSO) is a recommended adjuvant for the newly registered herbicide topramezone in China and also in other countries of the world, but the mechanism of MSO enhancing topramezone efficacy is still not clear. Greenhouse and laboratory experiments were conducted to determine the effects of MSO on efficacy, solution property, droplet spread and evaporation, active ingredient deposition, foliar absorption and translocation of topramezone applied to giant foxtail (Setaria faberi Herrm.) and velvet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…In 2019, there was no difference in velvetleaf biomass reduction among the herbicide programs evaluated. Zhang et al (2013) reported 90% velvetleaf biomass reduction with topramezone at 15.84 g ai ha -1 plus 0.3% methylated seed oil. Hart (1997) reported halosulfuron-methyl at 9 g ai ha -1 plus dicamba at 140 g ai ha -1 plus crop oil concentrate or methylated seed oil 1% vol/vol resulted in 87% velvetleaf biomass reduction.…”
Section: Biomass Reductionmentioning
confidence: 99%
“…In 2019, there was no difference in velvetleaf biomass reduction among the herbicide programs evaluated. Zhang et al (2013) reported 90% velvetleaf biomass reduction with topramezone at 15.84 g ai ha -1 plus 0.3% methylated seed oil. Hart (1997) reported halosulfuron-methyl at 9 g ai ha -1 plus dicamba at 140 g ai ha -1 plus crop oil concentrate or methylated seed oil 1% vol/vol resulted in 87% velvetleaf biomass reduction.…”
Section: Biomass Reductionmentioning
confidence: 99%
“…Tolpyralate + atrazine + MSO provided the greatest control of GR Canada fleabane at 2 and 4 WAA, and waterhemp at 4 WAA. The increased herbicidal activity observed with the addition of MSO may be attributed to the greater absorption and retention of the herbicide on plant leaf as a result of various physical and chemical changes to the herbicide solution [31] [41]. Reduced surface tension and contact angle of spray droplets promote the penetration of herbicides through the leaf cuticle [31].…”
Section: Discussionmentioning
confidence: 99%
“…The increased herbicidal activity observed with the addition of MSO may be attributed to the greater absorption and retention of the herbicide on plant leaf as a result of various physical and chemical changes to the herbicide solution [31] [41]. Reduced surface tension and contact angle of spray droplets promote the penetration of herbicides through the leaf cuticle [31]. Herbicidal activity of topramezone and isoxaflutole, two other Group 27 herbicides, is also improved with the addition of MSO [31] [41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations